2003
DOI: 10.1095/biolreprod.102.010785
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Enhances Oxytocin-Induced Rhythmic Myometrial Contraction1

Abstract: Although smoking during pregnancy is one of the major risk factors of premature delivery, the underlying mechanism by which smoking causes premature delivery is unknown. In the present study, we examined the effects of smoking on uterine contractility induced by oxytocin and prostaglandin F(2alpha). Rats inhaled either cigarette smoke or room air from Day 14 to Day 16 of pregnancy through an inhalation apparatus for experimental animals (type "Hamburg II"). After the rats were killed on Day 17 of pregnancy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
3
16
2
2
Order By: Relevance
“…Although the mechanisms through which cigarette smoke cause preterm uterine contractions and preterm delivery have not been known, it is well known that OT and PG F 2a induce pregnant uterine contractions and preterm delivery (Takahashi et al 1980, Fuchs et al 1984, Ivanisevic et al 2001. We have recently demonstrated that inhalation of cigarette smoke for 3 days (seven cigarettes/day) by pregnant Wistar rats significantly reduces both fetal and placental weight (Egawa et al 2003), and confirmed that smoking during pregnancy is an important cause of low birth weight, as has often been reported. We have also demonstrated that the sensitivity of pregnant rat uterus to OT (but not PG F 2a ) was significantly increased in the smoking group in comparison with the control group, and the expression of OTR mRNA, but not FP mRNA, in the uterus was significantly increased in the smoking group (Egawa et al 2003).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Although the mechanisms through which cigarette smoke cause preterm uterine contractions and preterm delivery have not been known, it is well known that OT and PG F 2a induce pregnant uterine contractions and preterm delivery (Takahashi et al 1980, Fuchs et al 1984, Ivanisevic et al 2001. We have recently demonstrated that inhalation of cigarette smoke for 3 days (seven cigarettes/day) by pregnant Wistar rats significantly reduces both fetal and placental weight (Egawa et al 2003), and confirmed that smoking during pregnancy is an important cause of low birth weight, as has often been reported. We have also demonstrated that the sensitivity of pregnant rat uterus to OT (but not PG F 2a ) was significantly increased in the smoking group in comparison with the control group, and the expression of OTR mRNA, but not FP mRNA, in the uterus was significantly increased in the smoking group (Egawa et al 2003).…”
Section: Discussionsupporting
confidence: 80%
“…We have recently demonstrated that inhalation of cigarette smoke for 3 days (seven cigarettes/day) by pregnant Wistar rats significantly reduces both fetal and placental weight (Egawa et al 2003), and confirmed that smoking during pregnancy is an important cause of low birth weight, as has often been reported. We have also demonstrated that the sensitivity of pregnant rat uterus to OT (but not PG F 2a ) was significantly increased in the smoking group in comparison with the control group, and the expression of OTR mRNA, but not FP mRNA, in the uterus was significantly increased in the smoking group (Egawa et al 2003). However, it remains unclear whether the inhalation of cigarette smoke directly enhances the expression of OTR mRNA in the myometrium.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations